Introducing the DYNAMICS framework of moment-to-moment development in achievement motivation. (October 2022) - Moeller, Julia; Viljaranta, Jaana; Tolvanen, Asko; Kracke, Bärbel; Dietrich, Julia
Abstract: This article introduces a new theoretical and psychometric framework describing moment-to-moment development and inter-dependencies of achievement motivation in terms of the situated expectancy-value theory, by introducing dynamical systems concepts into this line of research. As a first empirical example of a study using this framework, we examined whether task values, costs, and success expectancies measured in a learning situation (time point t) predicted themselves and each other at the next situation (t + 1; 27 min later) within a weekly university lecture. Situational task values, expectancies, and costs were assessed using the experience sampling method in 155 university teacher training students during weekly lectures for one semester, with three surveys during each weekly lesson. Data were analyzed with multilevel cross-lagged structural equation models. There were significant auto-regressions from one learning situation to the next in success expectancies and effort costs, but not in intrinsic, utility, or attainment value nor emotional or opportunity costs. There were no significant cross-lagged effects from one situation to the next in any of the measured situated expectancy-value components. As a framework to integrate dynamical systems concepts into the research on situated learning motivation, we expect the proposed DYNAMICS framework to have a substantial impact on further theory development. Highlights: This article proposes the DYNAMICS framework of situated achievement motivation. This study examined situational expectancies, values, and costs. We tested autoregressive and cross-lagged paths from one moment to the next.